1991
DOI: 10.1016/0035-9203(91)90470-j
|View full text |Cite
|
Sign up to set email alerts
|

Trachoma and water use; a case control study in a Gambian village

Abstract: Trachoma is prevalent in many arid areas but data assessing the relationship between water use and trachoma are very scarce. This study compared 18 families having one or more active trachoma cases among the children with 16 trachoma-free families in the same village with respect to water use. Potential confounders such as family size, distance to water source, socio-economic indicators, and hygiene behaviour were assessed in the 2 groups. The families with trachoma were found to use significantly less water p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 6 publications
0
53
2
Order By: Relevance
“…Households in close proximity to their primary water sources experience less diarrhea (Gorter et al, 1991;Wang and Hunter, 2010) and trachoma (Marx, 1989;Golovaty et al, 2009). They also have been shown to spend less time collecting water (Aiga and Umenai, 2002), use greater quantities of water (Bailey et al, 1991;Polack et al, 2006), and practice improved hygiene behavior (Cairncross and Cliff, 1987;Curtis et al, 1995). Health benefits of hygiene reflect the Mills Reincke phenomenon (Sedgwick and MacNutt, 1908) of multiple health gains; for example, hygiene has been shown to reduce risk and prevalence of respiratory infections (Ryan et al, 2001;Rabie and Curtis, 2006), trachoma (Taylor et al, 1989;West et al, 1995), and diarrhea (Aung Myo and Thein, 1989;Cairncross et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Households in close proximity to their primary water sources experience less diarrhea (Gorter et al, 1991;Wang and Hunter, 2010) and trachoma (Marx, 1989;Golovaty et al, 2009). They also have been shown to spend less time collecting water (Aiga and Umenai, 2002), use greater quantities of water (Bailey et al, 1991;Polack et al, 2006), and practice improved hygiene behavior (Cairncross and Cliff, 1987;Curtis et al, 1995). Health benefits of hygiene reflect the Mills Reincke phenomenon (Sedgwick and MacNutt, 1908) of multiple health gains; for example, hygiene has been shown to reduce risk and prevalence of respiratory infections (Ryan et al, 2001;Rabie and Curtis, 2006), trachoma (Taylor et al, 1989;West et al, 1995), and diarrhea (Aung Myo and Thein, 1989;Cairncross et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…24,55 In The Gambia, after controlling for family size, distance to water, and other socioeconomic factors, families with trachoma appeared to use less water for washing children than did the control families without trachoma, regardless of the amount of water available for consumption. 56 These findings suggest that behavioral factors around water use may be more important for trachoma than the total amount of water available.…”
Section: Provision Of Watermentioning
confidence: 99%
“…32,33 A study in the Gambia showed that members of households that allocated a greater proportion of their water to hygiene had a reduced risk of trachoma compared with those who did not, thus providing additional support to the argument for promoting facedwashing to control trachoma. 34 This evidence led to an RCT of hygiene promotion to control trachoma 35 that -although some of the comparisons narrowly failed to achieve statistical significance -was considered sufficiently compelling by WHO to warrant inclusion as part of the integrated strategy.…”
Section: Facial Cleanliness and Envi--ronmental Improvementmentioning
confidence: 99%